Paintbox and easel used by artist, Hans Heysen (1883)
A folding paintbox with four extended attachments and a used artist's palette with a folding easel.
Title devised by cataloguer from information in the acquisition file.
Condition: Fair, rust on metal parts.
Several old luggage labels attached on top and bottom of paintbox; 2 loose labels in mylar, one with Nora Heysen's name on it in ink.
Also available online
Purchased in 2006; file NLA06/2167.
Paintbox and easel purchased from Hans Heysen's estate by his daughter, Nora Heysen.
Keywords: Heysen, Hans, -- Sir, -- 1877-1968 -- Collectibles; Artists -- Australia -- Equipment and supplies; Artists equipment